Pore throat characteristics of tight reservoirs by a combined mercury method: A case study of the member 2 of Xujiahe Formation in Yingshan gasfield, North Sichuan Basin - Wang Youzhi; Mao Cui; Li Qiang; Jin Wei; Zhu Simiao; Wang Xiandong; Wang Zhiguo; He Jiayin; Shen Jiagang; Zhu Yanping; Wang Ying; Wang Haiyan; et al. (Open Geosciences, 2021)
The complex pore throat characteristics are significant factors that control the properties of tight sandstone reservoirs. Due to the strong heterogeneity of the pore structure in tight reservoirs, it is difficult to characterize the pore structure by single methods. To determine the pore throat, core, casting thin sections, micrographs from scanning electron microscopy, rate-controlled mercury injection, and high-pressure mercury injection were performed in member 2 of Xujiahe Formation of Yingshan gasfield, Sichuan, China. The pore throat characteristics were quantitatively characterized, and the distribution of pore throat at different scales and its controlling effect on reservoir physical properties were discussed. The results show that there are mainly residual intergranular pores, intergranular dissolved pores, ingranular dissolved pores, intergranular pores, and micro-fractures in the second member of the Xujiahe Formation tight sandstone reservoir. The distribution range of pore throat is 0.018–10 μm, and the radius of pore throat is less than 1 μm. The ranges of pore radius were between 100 and 200 μm, the peak value ranges from 160 to 180 μm, and the pore throat radius ranges from 0.1 to 0.6 μm. With the increase of permeability, the distribution range of throat radius becomes wider, and the single peak throat radius becomes larger, showing the characteristic of right skew. The large throat of the sandy conglomerate reservoir has an obvious control effect on permeability, but little influence on porosity. The contribution rate of nano-sized pore throat to permeability is small, ranging from 3.29 to 34.67%. The contribution rate of porosity was 48.86–94.28%. Therefore, pore throat characteristics are used to select high-quality reservoirs, which can guide oil and gas exploration and development of tight sandstone reservoirs.